Synthesis And Study Of Some Pyrazole Derivatives As Anti Tubercular Agent - VIMAL I PATEL; DR.BHAVESH PATEL (International Journal of Pharma and Bio Sciences, 2010)
The present work deals with evaluation of anti-tubercular activity of various aldehyde derivatives synthesized by Claisen-Schmidt condensation method. The formation of pyrazole derivatives by reaction with phenyl isothiocyanate was also attempted. The synthesized derivatives were screened for anti-tubercular activity and the compounds. All the Compounds characterized on the basis of their IR, MASS, 1H NMR spectroscopic data analysis.